2022
DOI: 10.3390/cells11071186
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxic Astrocytes Directly Converted from Sporadic and Familial ALS Patient Fibroblasts Reveal Signature Diversities and miR-146a Theragnostic Potential in Specific Subtypes

Abstract: A lack of stratification methods in patients with amyotrophic lateral sclerosis (ALS) is likely implicated in therapeutic failures. Regional diversities and pathophysiological abnormalities in astrocytes from mice with SOD1 mutations (mSOD1-ALS) can now be explored in human patients using somatic cell reprogramming. Here, fibroblasts from four sporadic (sALS) and three mSOD1-ALS patients were transdifferentiated into induced astrocytes (iAstrocytes). ALS iAstrocytes were neurotoxic toward HB9-GFP mouse motor n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 132 publications
(252 reference statements)
0
22
0
Order By: Relevance
“…Our previous studies identified elevated levels of miR-124, miR-125b and miR-21 in PSEN1 mutant iPSC-derived neurons and SH-SY5Y- APP695 Swedish neuroblastoma cells [ 25 , 39 ]. Such alterations in these inflammatory-associated miRNAs and their modulations are important for recovering dysregulated biological functions in target cells toward regenerative medicine, as we demonstrated [ 41 , 82 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 93%
“…Our previous studies identified elevated levels of miR-124, miR-125b and miR-21 in PSEN1 mutant iPSC-derived neurons and SH-SY5Y- APP695 Swedish neuroblastoma cells [ 25 , 39 ]. Such alterations in these inflammatory-associated miRNAs and their modulations are important for recovering dysregulated biological functions in target cells toward regenerative medicine, as we demonstrated [ 41 , 82 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 93%
“…Guttenplan and colleagues performed triple knockout of IL-1α, TNFα, and C1q and observed a reduction in astrogliosis and longest extension of lifespan ever reported in SOD1 G93A mice [ 98 ]. Collectively, ALS astrocytes play a role in the progression of disease by secreting cytokines for neuroinflammation and protein aggregation, and there is accumulating evidence suggesting that altering the secretory profiles of astrocytes can delay the progression of ALS [ 26 , 87 , 99 ].…”
Section: Astrocytes Remodel Their Secretome In Alsmentioning
confidence: 99%
“…ALS astrocytes are known to take on an inflammatory reactive state [ 24 ], which triggers the release of pro-inflammatory cytokines and chemokines that initiate an inflammatory cascade that results in neuronal damage and death [ 25 ]. An increasing body of evidence also suggests contribution of multiple other bioactive molecules to ALS astrocyte-mediated toxicity, such as lipids, metabolites, microRNAs and even extracellular matrix proteins [ 24 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…microRNAs (miRNAs) have been defined as important regulatory molecules for gene expression, and their dysregulation in ALS can be modulated toward the recovery of cell function and an increase in mSOD1 mouse lifespan, as reviewed in [ 7 ]. Furthermore, these molecules can be released into the secretome as free species or encapsulated in small extracellular vesicles (sEVs) [ 8 , 9 , 10 , 11 ] and internalised by neighbouring cells, also having the ability to influence distant cells and the extracellular environment [ 11 , 12 ]. Since ALS is characterized as a neuroinflammatory and neurodegenerative disease, we have focused on the study of inflammatory-associated (inflamma)-miRNAs, including miR-124, miR-155, and miR-146a, which were shown to be differentially expressed at the cellular and regional levels [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors claimed that it has potential for autologous treatment in ALS. In addition, many studies have elucidated the therapeutic promise of miRNAs after their modulation, either by overexpression or suppression in mSOD1 mice and in astrocytes directly converted from patient somatic cells [ 8 , 20 ]. Some works have evidenced an increased lifespan of mice [ 20 , 21 , 22 , 23 ], followed by an improvement in MN survival [ 21 , 22 ] and muscle strength [ 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%